High-intensity exercise training induces mitonuclear imbalance and activates the mitochondrial unfolded protein response in the skeletal muscle of aged mice - Cordeiro, Andre Victor; Peruca, Guilherme Francisco; Braga, Renata Rosseto; Bricola, Rafael Santos; Lenhare, Luciene; Rodrigues Silva, Vagner Ramon; Anaruma, Chadi Pellegrini [UNESP]; Katashima, Carlos Kiyoshi; Crisol, Barbara Moreira; Barbosa, Lucas Torres; Simabuco, Fernando Moreira; Ramos da Silva, Adelino Sanchez; et al. (Springer, 2020)
The impairment of mitochondrial metabolism is a hallmark of aging. Mitonuclear imbalance and the mitochondrial unfolded protein response (UPRmt) are two conserved mitochondrial mechanisms that play critical roles in ensuring mitochondrial proteostasis and function. Here, we combined bioinformatics, physiological, and molecular analyses to examine the role of mitonuclear imbalance and UPRmt in the skeletal muscle of aged rodents and humans. The analysis of transcripts from the skeletal muscle of aged humans (60-70 years old) revealed that individuals with higher levels of UPRmt-related genes displayed a consistent increase in several mitochondrial-related genes, including the OXPHOS-associated genes. Interestingly, high-intensity interval training (HIIT) was effective in stimulating the mitonuclear imbalance and UPRmt in the skeletal muscle of aged mice. Furthermore, these results were accompanied by higher levels of several mitochondrial markers and improvements in physiological parameters and physical performance. These data indicate that the maintenance or stimulation of the mitonuclear imbalance and UPRmt in the skeletal muscle could ensure mitochondrial proteostasis during aging, revealing new insights into targeting mitochondrial metabolism by using physical exercise.
Keywords: Aging; UPRmt; Skeletal muscle; Exercise; Mitonuclear imbalance